Analisis Laju Korosi Sambungan Baja ASTM-A36 dengan Variasi Arus Pengelasan dalam Media Air Laut - Fauzi Widyawati, Widyawati (Jurnal Teknik, 2023)
Steel plate is a component that has an important role in making the design, especially on the hull of the ship. In the manufacture of shipbuilding, it is impossible to form without the welding process. Welded steel will experience changes in grain size differences which result in the emergence of anode and cathode areas which are potential for corrosion. This study aims to examine the corrosion behavior of ASTM A36 steel which has been welded using SMAW welding with variations in welding current in seawater medium for seven days. To study the corrosion properties of ASTM A36 steel welds, 15 specimens were welded with 5 variations of welding current, namely 60 A, 70 A, 80 A, 90 A, and 100 A. Corrosion was measured according to the ASTM G31-72 standard with the weight loss method. The results showed that the most efficient welding current was at a welding current of 70 A with an average corrosion rate of 20.8970 mpy. The highest corrosion rate was found in the welding current sample of 100 A with an average corrosion rate of 28.2327 mpy.